EMPOWERING HOUSEWIVES FOR FAMILY ECONOMIC RESILIENCE IN NAGARI BALAIGURAH, WEST SUMATRA - Endrizal, Endrizal; Suharti; Kahanna, Mutia (Kirana Publisher, 2024)
For women who are housewives, developing their potential should also be something that needs to be done, especially for those who depend on their husbands for economic income. Such is the case in nagari Balaigurah, District IV angkek, Agam Regency, West Sumatra. Most housewives there have not even realised their potential. This reason is the background of the counselling activities aimed at motivating and exploring the potential of housewives in Nagari Balaigurah, District IV Angkek. The method used in this research is qualitative method. Data was collected by means of in-depth interviews, documentation and Focus Group Discussions. Through this research, it is found that the involvement of Nagari as a stakeholder is an undeniable element to achieve the expected results so that later the potential of housewives who have been explored can synergise with the Nagari programme.